A Study of Space Allocation and Optimization of Traditional Chinese Medical Institutions Based on Medical Service Radius: a Case Study of Zengcheng District, Guangzhou City - LI Chengcheng, ZHOU Shangcheng, HE Kaiyue, LIU Ailing, LIANG Shanshan, GAO Jing, ZHONG Ailin (Zhongguo quanke yixue, 2025)
Background As China's Traditional medicine is included in the ICD-11 code, the rational allocation of basic TCM medical resources is the guarantee to promote the integration of traditional Chinese medicine and western medicine and the universal coverage of high-quality medical resources. The uneven layout and service capabilities of grassroots medical institutions have led to a widespread imbalance in the supply and demand of medical resources in urban and rural areas. Objective Understand the development status of traditional Chinese medicine services in rural areas of China, scientifically evaluate the coverage and accessibility of grassroots traditional Chinese medicine diagnosis and treatment, provide new ideas for optimizing the spatial resource allocation of grassroots traditional Chinese medicine services, and propose optimization strategies accordingly. Methods Based on the seventh national population census data and path planning data, the concept of medical service radius is introduced to calculate the diagnosis and treatment scope of different levels of traditional Chinese medicine medical institutions under walking mode. Using methods such as spatial kernel density index and spatial standard deviation ellipse to reveal the spatial fairness of the supply and demand capacity of traditional Chinese medicine medical services. Based on the above results, propose types and measures for optimizing the layout of traditional Chinese medicine medical resources. Results As of 2022, there are a total of 699 medical institutions in Zengcheng District, including 18 traditional Chinese medicine medical institutions with beds. There were significant differences in the distribution of beds in traditional Chinese medicine medical institutions in different townships and streets. Meanwhile, the number of beds per thousand population in Zhongtan Town was 14.31, ranking first among all streets. The number of beds per thousand people in Yongning Street ranks last, with only 0.89 beds. Traditional Chinese medicine medical institutions in Zengcheng District had shown a clear dual center pattern, with weak accessibility to traditional Chinese medicine services for residents in the central part of Zhongxin Town, the northern part of Paitan Town, and the southwestern part of Shitan Town. The supply capacity of traditional Chinese medicine services varies greatly among different townships. There was still a certain degree of inconsistency between the spatial distribution of traditional Chinese medicine medical institutions and the overall spatial clustering of urban residents. There were differences in the radius of traditional Chinese medicine services between different townships. Conclusion Since the implementation of the development strategy of traditional Chinese medicine, China's Traditional medicine has been protected and developed. We should adopt a more scientific strategy to closely integrate traditional Chinese medicine services with the development of the city and the needs of residents. We should actively adopt a differentiated strategy of increasing facility points, combining resource transfer and sinking, and integrating traditional Chinese medicine information technology for diagnosis and treatment across regions, gradually achieving a true strategy of full coverage and equal emphasis on traditional Chinese and Western medicine.